User Experience in Cloud Computing Services-Based LMS: a Case Study - Pramono, Luthfan Hadi (Universitas Bina Darma, 2023)
This research explores user experiences with Learning Management Systems (LMS) in the context of online education, focusing on the Google Classroom application. Conducted at SDIT Salsabila 4 Jetis, Indonesia, the study navigates challenges faced during the transition to remote learning, particularly amid the COVID-19 pandemic. Evaluating features such as media upload, assignment scheduling, quizzes, and grading, the research identifies key areas of user engagement that require optimization. Effective teacher-student communication emerged as pivotal, underlining the need for tailored training programs to enhance teachers' proficiency with LMS features. Network stability also significantly influenced user experience. The study's insights emphasize the LMS's potential as a powerful educational tool and highlight specific areas for improvement. Recommendations include broader data collection across institutions, facilitating a nuanced understanding of LMS adoption curves. Moreover, targeted training initiatives are crucial, ensuring educators' comprehensive grasp of LMS functionalities. These findings provide a foundational framework for refining online education practices, promoting a more seamless and effective learning environment for educators and students alike.